Network Dependency in Migration Flows – A Space-time Analysis for Germany since Re-unification - Timo Mitze (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2010)
The contribution of this paper is to analyse the role of network interdependencies in a dynamic panel data model for German internal migration flows since re-unification. So far, a capacious account of spatial patterns in German migration data is still missing in the empirical literature. In the context of this paper, network dependencies are associated with correlations of migration flows strictly attributable to proximate flows in geographic space. Using the neoclassical migration model, we start from its aspatial specification and show by means of residual testing that network dependency effects are highly present. We then construct spatial weighting matrices for our system of interregional flow data and apply spatial regression techniques to properly handle the underlying space-time interrelations. Besides spatial extensions to the Blundell-Bond (1998) system GMM estimator in form of the commonly known spatial lag and unconstrained spatial Durbin model, we also apply system GMM to spatially filtered variables. Finally, combining both approaches to a mixed spatial filteringregression specification shows a remarkably good performance in terms of capturing spatial dependence in our migration equation and at the same time qualify the model to pass essential IV diagnostic tests. The basic message for future research is that space-time dynamics is highly relevant for modelling German internal migration flows. – – Die Arbeit untersucht die Rolle von räumlichen Interdependenzen in Netzwerkdaten am Beispiel eines dynamischen Paneldaten Modells für interne Wanderungsbewegungen in Deutschland seit der Wiedervereinigung. Die Analyse von expliziten räumlichen Mustern bei der Betrachtung von innerdeutschen Migrationsflüssen fehlt bisher in der empirischen Literatur. Anhand eines raumlosen Migrationsmodells wird zunächst gezeigt, dass vernachlässigte Netzwerkeffekte von Bedeutung für die Interpretation struktureller Zusammenhänge in Migrationsgleichungen sind. Durch die geeignete Spezifikation von räumlichen Gewichtungsmatrizen und die Anwendung verschiedener räumlich-ökonometrischer Schätzverfahren für dynamische Modelle mit Paneldaten kann schließlich eine integrierte Raum-Zeit-Betrachtung vorgenommen werden. Die Ergebnisse zeigen, dass die erweiterten Modelle in der Lage sind, räumliche Netzwerk- und Zeitanpassungseffekte in Migrationsflüssen abzubilden und eine gute Gesamtperformance aufweisen. Die grundsätzliche Schlussfolgerung für zukünftige Forschungsarbeiten daraus ist, dass bei der Analyse innerdeutscher Migrationsflüsse zeitliche und räumliche Abhängigkeiten berücksichtigt werden müssen.
Keywords: R23; C31; C33; 330; internal migration; dynamic panel data; Spatial Durbin Model; GMM